TiO2-carbon xerogel composites as supports in the preparation of Pt catalysts for selective hydrogenation - Gomes, Helder (2010)
In the last decades, considerable efforts have been devoted to the development of heterogeneous catalysts able to perform efficient selective hydrogenation of the carbonyl function in α,β-unsaturated aldehydes, to yield the corresponding unsaturated alcohols, which are important intermediates in organic synthesis of fine chemicals for several industries, such as flavor, fragrance and pharmaceutical. Unfortunately, high selectivities towards these alcohols are difficult to achieve, since thermodynamics favors the hydrogenation of the C=C over the C=O bond and due to kinetic reasons, as the reactivity of the olefinic bond is higher than that of the carbonyl.